SIMULATION OF SOCIO-ECONOMIC DEVELOPMENT OF REGIONS - Elena N. Volkova; Mikhail V. Karmanov (Статистика и экономика, 2016)
Simulation of different socio-economic phenomena and processes reveals the basic relationship between the various indicators. The article presents the results of regression analysis, which is possible to determine the inuence of some socio-economic factors on the level of development of the Moscow region. The results obtained allowed to form a series of conclusions and a proposal aimed at improving the level of economic development of the region.